Roger D. Hansen. The politics of Mexican development. Baltimore, [Md.] : The John Hopkins Press, 1971. 276 p. - Villa Aguilera, Manuel (Estudios Demográficos y Urbanos, 1972)
ROGER D. HANSEN, The Politics of Mexican Development, Baltimore, The John Hopkins Press, 1971.